PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT Adenium sp ASAL BIJI - Agita, Rendi; Budi, Setia; Zulfita, Dwi (Jurnal Sains Pertanian Equator, 2015)
This experiment aims to determine the composition of the best growing media for the growth of seedling of Adenium sp originated from seed. It was conducted on February 3rd 2014 to October 6th 2014 at on Jalan Budi Utomo, Komplek Surya Kencana II Block G.8, District of North Pontianak. The experiment used a completely randomized design (CRD), which consists of 4 treatments with 6 replicates and each treatment consisted of 3 samples that contained 72 plants sampled plants. Such treatment is peat: sand: chicken manure (1: 1: 1 v / v / v), husk fuel: sand: chicken manure (1: 1: 1 v / v / v), cocopeat : sand : chicken manure (1: 1: 1 v / v / v), sawdust: sand: chicken manure (1: 1: 1 v / v / v). The increase of variables measured were plant height (cm), the increase of leaf number (strands), total leaf area (cm2), stem diameter (cm), and root volume (cm3). Result showed that composition growth media has significant effect on increase plant height at months 2nd, 3rd, and root volume while stem diameter, and the increase of leaf number at months 1st. 2nd, 3rd does not significant effect. Keywords: Adenium sp, peat, roasted husks, cocopeat, sawdust, sand, chicken manure.